Cross- analyzing the opinions and experiences of nurses, physiotherapists, dentists, midwives, and pharmacists with respect to addictive disorder screening in primary care: A qualitative study - Agathe Edeline; Amelie Tripault; Jean Pierre Lebeau; Maxime Pautrat (PLoS ONE, 2025)
Early addiction disorders screening is recommended in primary care. The goal of health system reform is to include allied health professionals in this screening. The appropriation of their new role has not yet been explored. The main aim of this study was to examine the perspective of allied health professionals in primary care on the screening of addictive disorders. This qualitative study inspired by the grounded theory was carried out between August 2018 and July 2019. Semi-structured individual interviews and focus groups were organized to include of primary care health professionals (physiotherapist, nurse, midwife, pharmacist, and dentist). Thirteen semi-structured individual interviews and four focus groups were recorded and coded. The paramedics described the advantages of their professions for the detection of addictions: home visits, prescription history, habit of intimate subjects, close consultations, etc. Despite daily practice-specific observation posts, they sometimes remained silent witnesses, and their helplessness hindered identification. They felt both closer to the patients and less legitimate than the doctors in dealing with addictions. Finally, their desire for a multidisciplinary approach was limited by the fear of disturbing the doctor and the confusion between betrayal and medical secrecy. Paramedical professionals claimed to have a complementary role to play in identifying addictions. Their reluctance echoed the concept of self-censorship, already described in studies with addictologists and patients. These results must be compared with the opinions of general practitioners and patients.